2020
DOI: 10.1021/acscatal.0c02189
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Transfer of Pseudaminic Acid (Pse5Ac7Ac) Using Promiscuous Sialyltransferases in a Chemoenzymatic Approach to Pse5Ac7Ac-Containing Glycosides

Abstract: Pseudaminic acid (Pse5Ac7Ac) is a nonmammalian sugar present on the cell surface of a number of bacteria including Pseudomonas aeruginosa, Campylobacter jejuni and Acinetobacter baumannii. However, the role Pse5Ac7Ac plays in host-pathogen interactions remains underexplored, particularly compared to its ubiquitous sialic acid analogue Neu5Ac. This is primarily due to a lack of access to difficult to prepare Pse5Ac7Ac glycosides. Herein we decribe the in vitro biocatalytic transfer of an activated Pse5Ac7Ac don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…Several glycoconjugates containing a number of Pse derivatives that differ in their N5 or N7 substitutions have been identified to date in various drug‐resistant pathogens, and a connection between the Pse and virulence has been demonstrated. [ 16 , 17 ] Chemical probes for identification of Pse‐expressing bacteria are therefore highly appealing and can pave the way for anti‐virulence agents that inhibit Pse biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Several glycoconjugates containing a number of Pse derivatives that differ in their N5 or N7 substitutions have been identified to date in various drug‐resistant pathogens, and a connection between the Pse and virulence has been demonstrated. [ 16 , 17 ] Chemical probes for identification of Pse‐expressing bacteria are therefore highly appealing and can pave the way for anti‐virulence agents that inhibit Pse biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on inversion reactions in the synthesis of 2,4-di-azido-2,4-di-deoxy- α - L -Rha recommended harsh conditions (110°C in DMF/HMPA); however, the yield was not satisfactory (58%/69%), and no detailed explanations were given ( Sanapala and Kulkarni, 2016a ; Flack et al, 2020 ). In our study, using 3- O -acetyl- α - L -Fuc 1 as reactant and TBAN 3 (5.0 equiv.×2) in the double inversion process resulted in a mixture of 2,4-di-azido-3- O -acetyl-2,4,6-trideoxy- α - L -Glu 2 and 2,4-di-azido-3- O -acetyl-2,4-di-deoxy- α - L -Rha 3 ( Table 1 , Entry 1, NMR ratio 51 / 49 , 2 : 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…To prepare di-NAc sugars to obtain nonulosonic acid precursors, we need to synthesize 6-deoxy- L -AltdiNA 40 ( Scheme 4 ). Fascione’s group used the Lattrell–Dax reaction ( Guo and O'Doherty, 2007 ; 2008 ) with β -Rha 34 as the substrate and found that the epimerization product 35 was obtained in moderate yield in the TBANO 2 /acetonitrile system (46%) ( Flack et al, 2020 ). They also found α -Rha 32 was inefficient for the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations